Bmal1 haploinsufficiency impairs fear memory and modulates neuroinflammation via the 5-HT2C receptor - Weifen Li; Weifen Li; Shengnan Mou; Tahir Ali; Tahir Ali; Tianxiang Li; Yan Liu; Shupeng Li; Shupeng Li; Shupeng Li; Xiaoming Yu; Zhi-Jian Yu (Frontiers Media S.A., 2024)
BackgroundBMAL1, a key regulator of circadian rhythms, plays a multifaceted role in brain function. However, the complex interplay between BMAL1, memory, neuroinflammation, and neurotransmitter regulation remains poorly understood. To investigate these interactions, we conducted a study using BMAL1-haplodeficient mice (BMAL1+/−).MethodsWe exposed BMAL1+/− mice to behavioral assessments including cued fear conditioning, new objection recognition (NOR) test, and Y-maze test to evaluate BMAL1+/− haplodeficiency impact on memory. Furthermore, biochemical changes were analyzed through western blotting, and ELISA to explore further the mechanism of BMAL1+/− in memory, and neuroinflammation.ResultsWe found that BMAL1 haploinsufficiency led to deficits in cued fear learning and memory, while spatial memory and object recognition remained intact. Further analysis revealed dysregulated neurotransmitter levels and alterations in neurotransmitter-related proteins in the prefrontal cortex of BMAL1+/− mice. Pharmacological interventions targeting dopamine uptake or the 5-HT2C receptor demonstrated that inhibiting the 5-HT2C receptor could rescue fear learning and memory impairments in BMAL1+/− mice. Additionally, we observed downregulation of the inflammasome and neuroinflammation pathways in BMAL1+/− mice, which is validated by inflammation mediator lipopolysaccharide (LPS) administration.ConclusionThese findings highlight that BMAL1 haploinsufficiency leads to deficits in fear learning and memory, which are linked to alterations in neurotransmitters and receptors, particularly the 5-HT2C receptor. Targeting the 5-HT2C receptor may offer a potential therapeutic strategy for mitigating cognitive impairments associated with BMAL1 dysfunction.